Amnesty International Canada and British Columbia Civil Liberties Association v. Chief of Defence Staff for the Canadian Forces and Others. (2014) - Unknown
Abstract : 311 Jurisdiction — Extraterritorial jurisdiction — Canadian Charter of Rights and Freedoms — Whether having extraterritorial application — Whether Charter applying during armed conflict in Afghanistan to detention of non-Canadians by Canadian Forces or their transfer to Afghan authorities — Section 32(1) of Charter — Interpretation of jurisdictional reach by courts — Judgments of Supreme Court — Hape — Khadr (No 1) — Whether Canada having effective control of detention facilities — Whether Afghanistan consenting to application or enforcement of Canadian law — Afghan compact — Applicable law — International law — International humanitarian law — Whether Charter applying if detainees at substantial risk of torture if transferred to Afghan authorities — General rule against extraterritorial application of Charter — Whether fundamental human rights exception to general rule — Concepts of territoriality and comity — Relevance of all circumstances Human rights — Freedom from torture — Non-Canadian nationals detained by Canadian Forces in Afghanistan during armed conflict — Canadian Charter of Rights and Freedoms — Whether applicable if detainees at substantial risk of torture if transferred to Afghan authorities — General rule against extraterritorial application of Charter — Whether fundamental human rights exception to general rule — Whether detainees having rights under Charter — Applicable law — International humanitarian law — Afghan Constitution Territory — Territorial sovereignty — Armed conflict in Afghanistan — Detention of non-Canadians by Canadian Forces — Whether Canadian Forces' authorities having effective control of detention facilities — Banković — Canadian Forces in Afghanistan at request of Afghan Government — Whether Afghanistan consenting to extension of Canadian law over non-Canadian nationals — Afghan Compact — Whether Canadian Charter of Rights and Freedoms having extraterritorial application War and armed conflict — Armed conflict in Afghanistan — Detention of non-Canadians by Canadian Forces — Law applicable to detainees — Whether Afghanistan consenting to extension of Canadian law over non-Canadian nationals — Whether Canadian Forces occupying force — Whether Canadian Forces' authorities having effective control of detention facilities — Banković — Afghan Compact — International humanitarian law — Applicability of Canadian Charter of Rights and Freedoms — The law of Canada